A novel HD‐ZIP IV/MIXTA complex promotes glandular trichome initiation and cuticle development in Artemisia annua. Issue 2 (29th January 2018) - Yan, Tingxiang; Li, Ling; Xie, Lihui; Chen, Minghui; Shen, Qian; Pan, Qifang; Fu, Xueqing; Shi, Pu; Tang, Yueli; Huang, Huayi; Huang, Yiwen; Huang, Youran; et al.
Summary: Glandular trichomes and cuticles are both specialized structures that cover the epidermis of aerial plant organs. The former are commonly regarded as 'biofactories' for producing valuable natural products. The latter are generally considered as natural barriers for defending plants against abiotic and biotic stresses. However, the regulatory network for their formation and relationship remains largely elusive. Here we identify a homeodomain‐leucine zipper (HD‐ZIP) IV transcription factor, AaHD8, directly promoting the expression of AaHD1 for glandular trichome initiation in Artemisia annua . We found that AaHD8 positively regulated leaf cuticle development in A. annua via controlling the expression of cuticle‐related enzyme genes. Furthermore, AaHD8 interacted with a MIXTA‐like protein AaMIXTA1, a positive regulator of trichome initiation and cuticle development, forming a regulatory complex and leading to enhanced transcriptional activity in regulating the expression of AaHD1 and cuticle development genes. Our results reveal a molecular mechanism by which a novel HD‐ZIP IV/MIXTA complex plays a significant role in regulating epidermal development, including glandular trichome initiation and cuticle formation.